Fertilization, irrigation and pasture sown to improve herbage production and quality in Nothofagus antarctica silvopastoral systems in southern Patagonia. - Gargaglione, Veronica Beatriz (2024)
Nothofagus antarctica forest extends from 46 to 56° south latitude and its main use has been as silvopastoral systems (SPS). Several studies have characterized understory of N. antarctica SPS. However, other practices like pasture sowing, irrigation and fertilization, to improve understory yield, remains little documented. The aim of this work was to compare dry matter (DM) production and quality of natural understory vs. implanted pastures under different water and nutrient conditions. An experiment with fifteen plots of 6×6 m was established in a strip-split plot design, with species as the main factor, water as the sub-plot factor (rainfed vs. irrigated) and fertilizer application level as sub-sub-plot factor (low, medium and high). The species evaluated were: Dactylis glomerata, Bromus catharticus, Trifolium pratense, T. repens and natural understory. Total dry matter (DM) production, leaf N concentration and digestibility were measured after 1 and 2 years of experiment establishment. Significant differences were found in DM according to species and fertilization treatments. The highest DM production was for T. pratense with medium fertilization level (5194 kg DM ha−1), followed by D. glomerata with 200 kg N ha−1 (4984 kg DM ha−1). Natural understory increased DM with nitrogen fertilization from 1427 to 3980 kg DM ha−1. In terms of quality, T. repens had the highest digestibility values. This study showed that pure pastures of T. pratense or D. glomerata accompanied by N fertilization are viable options to increase forage yield and quality in N. antarctica SPS.